Awareness regarding COVID-19 preventive measures and reasons for non-adherence among people in an urban area of mid-Kerala - Vijayan, Anagha Shylaja; Viswambharan, Jaya Koothupalakkal; Ravindran, Reshmy Kandampully (International Journal Of Community Medicine And Public Health, 2022)
Background: COVID-19 pandemic is a major challenge to the entire world. Since it is droplet borne preventive measures can reduce the transmission effectively. So, assessing awareness regarding COVID-19 preventive measures and reason for non-adherence to them will be really helpful. Methods: Data has been collected from 502 patients attending an urban centre of mid-Kerala after obtaining informed written consent. Results: Mean age of study population was 52.96±SD 14.52 years ranging from 18 to 89. Males were 52%. Majority of the participants 467(93%) were aware about COVID-19 preventive measures. The main source of information was television and newspaper. Awareness was less among those with low educational status (90.9%) and among house wives (90.2%). Main reasons for non-adherence were constraints of space for social distancing, 18 (3.6%) forgetting to adhere 28 (5.6%) for avoiding unnecessary touching and not feeling the importance of adherence 10 (2%). Conclusions: Majority of study participants were aware about COVID-19 preventive measures even if a small proportion were not practicing it and were not aware about it. Therefore, along with the measures to tackle the reasons for non-adherence, programmes on health education regarding COVID-19 preventive measures should be planned and implemented focusing on these vulnerable groups for successful prevention of the disease.